(1/2011*1/2010*1/2009*...1/3*1/2*1)∧2011*(2011*2010*2009*...
1个回答
=(1/2011!)^2011*(2011!)^2011
=1^2011=1
相关问题
计算:(1/2+2009/2010+2010/2011)*(2009/2010+2010/2011+2011/2012)
1/2011+2/2011+3/2011+…+2009/2011+2010/2011=?
(2009×2010-1)/(2009+2008×2010)+(2010×2011-1)/(2010+2009×2011
2010+2009×2011/2010×2011-1—2009+2008×2010/2009×2010-1
|1/2012-1/2011|+|1/2011-1/2010|+|1/2010-1/2009|-|1/2009-1/20
|1/2009-1/2010|+|1/2010-1/2011|+|1/2011-1/2012|
|1∕2009-1∕2010|+|1∕2010﹣1∕2011|﹢|1∕2011-1∕2012|=
(1/2010*1/2009*1/2008*...*1/3*1/2*1)^2011*(2010*2009*2008*..
计算:|1/2012-1/2011|+|1/2011-1/2010|+|1/2010-1/2009||+…+|1/3-1
2009/(2009又2010分之2009)/(1/2*3+1/3*4+...+1/2010*2011)